Utilization of Artificial Intelligence Tools in Medical Education among Undergraduate Medical Students at a Public Medical School in Sarawak, Malaysia - Chai, Chau Chung; Md Mizanur, Rahman; Karen Shendy, Sampson Sambong; Siti Nursyazwani, Azmi Murad; Hariz Hizami, Hatta; Chai Zi, Penny Chen (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2024)
Introduction: Artificial Intelligence (AI) is increasingly becoming an integral part of medical education, offering potential opportunities for enhancing learning experiences. Despite its growing relevance, the utilization of AI tools in medical education among medical students in Sarawak, Malaysia, remains underexplored.